THE ASSOCIATION BETWEEN CENTRAL SEROUS CHORIORETINOPATHY AND SLEEP APNEA: A Nationwide Population-Based Study. Issue 10 (October 2020) - Liu, Pei-Kang; Chang, Yo-Chen; Tai, Ming-Hong; Tsai, Rong-Kung; Chong, Inn-Wen; Wu, Kwou-Yeung; Wu, Wen-Chuan; Hsu, Chung-Yao; Tsai, Ming-Ju
Abstract : Purpose: To identify the association between sleep apnea (SA) and central serous chorioretinopathy (CSC). Methods: In this nationwide population-based study using the Taiwan National Health Insurance Database, we enrolled adult patients with a diagnosis of SA and matched each patient to 30 age- and gender-matched control subjects without any SA diagnosis. Using Poisson regression analyses, the incidence rate of CSC was compared between SA patients and control subjects. Results: A total of 10, 753 SA patients and 322, 590 control subjects were identified. After adjusting for age, gender, residency, income level, and comorbidities, the incidence rate of CSC was significantly higher in SA patients than in the control subjects (adjusted incident rate ratio for probable SA: 1.2 [95% CI: 1.1–1.4], P < 0.0001). Analyses of the propensity score-matched subpopulations also confirmed our findings. Risk factors for CSC in SA patients included male gender, age ⩽50 years, higher income, presence of heart disease, absence of chronic pulmonary disease, and presence of liver disease. In SA patients, those who had received continuous positive airway pressure titration had a significantly lower incidence rate of CSC than the others. Conclusion: Our study revealed a significantly higher incidence rate of CSC in SA patients compared with the control subjects. Abstract : Supplemental Digital Content is Available in the Text.This nationwide population-based cohort study revealed a significantly higher incidence rate of central serous chorioretinopathy in patients with sleep apnea than in control subjects. Treatment with continuous positive airway pressure may decrease the risk of central serous chorioretinopathy in sleep apnea patients.